2020
DOI: 10.1089/dia.2019.0489
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Pediatric Telediabetes Service Models

Abstract: Telediabetes may improve patient access to clinicians who specialize in the management of pediatric diabetes. Due to the diversity of telehealth modes, many different service models for pediatric telediabetes have been developed. This review describes pediatric telediabetes service models identified in the literature, investigates the reported changes in HbA1c of these interventions, and describes enablers and barriers to implementing a telediabetes service. Evaluation of current literature may inform the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 38 publications
4
39
0
Order By: Relevance
“…The main results are in line with a recent systematic review published by De Guzman et al [4] on 29 telemedicine studies in the field of paediatric diabetes care. The majority of these studies focussed on metabolic outcomes, while only few assessed participants' or professionals' satisfaction.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The main results are in line with a recent systematic review published by De Guzman et al [4] on 29 telemedicine studies in the field of paediatric diabetes care. The majority of these studies focussed on metabolic outcomes, while only few assessed participants' or professionals' satisfaction.…”
Section: Discussionsupporting
confidence: 90%
“…as being discussed face-to-face. Recent studies have shown that telemedicine in diabetes care might improve self-management, therapy engagement, and metabolic outcomes [1,3,4]. It is assumed that patients and diabetes teams have positive attitudes about video consultation if they have the means to set it up technically and carry it out.…”
Section: Introductionmentioning
confidence: 99%
“…While discussions about remote telemedicine are rapidly increasing due to the pandemic, a number of studies have previously investigated the potential benefits of telemedicine in diabetes care 6,9,10 . In a systematic review of 29 studies in the field of paediatric diabetes care, 7 it was concluded that telemedicine has the potential to facilitate patient monitoring and can improve short‐term glycaemic control in some contexts. It has also been suggested that virtual diabetes care may prove effective in aiding behavioural change, as well as providing social and psychological support 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Usability refers to the extent to which a product is used “to achieve specified goals with effectiveness, efficiency and satisfaction in a specified context” [10] . Usability has been identified as an enabler of successful telehealth care, and may reduce burden on patients and clinicians [11] ; however, there remains limited information about the usability of virtual technologies for pediatric patients and their families, especially during a pandemic.…”
Section: Introductionmentioning
confidence: 99%